2022
DOI: 10.1108/tqm-09-2021-0264
|View full text |Cite
|
Sign up to set email alerts
|

Top management team heterogeneity and economic performance: a micro-foundations perspective of academic business venturing

Abstract: PurposeThis research focuses on the relationship between Top Management Team heterogeneity (TMT) and University Spin-Offs (USOs) economic performance according to a micro-foundational perspective. The purpose consists in exploring whether a high academic representation in TMTs may improve USOs’ performance and how their competencies and backgrounds affect USOs’ economic success.Design/methodology/approachThe authors employed data from the Italian platform Netval to identify the entire population of USOs in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 134 publications
(350 reference statements)
0
3
0
Order By: Relevance
“…In the first step, data on the performance inputs of Italian TTOs were collected through the Netval database. The Netval database is a wellrecognized database that provides data on the technology transfer activities of all Italian universities, public research organization and research hospitals (Cucino et al, 2021;Hockaday and Piccaluga, 2021;Micozzi et al, 2021;Muscio et al, 2016;Sciarelli et al, 2022). In particular, Netval every year performs a survey of Italian universities, public research organizations, and research hospitals to monitor their technology transfer activities.…”
Section: Research Methodology 31 Sample and Data Collectionmentioning
confidence: 99%
“…In the first step, data on the performance inputs of Italian TTOs were collected through the Netval database. The Netval database is a wellrecognized database that provides data on the technology transfer activities of all Italian universities, public research organization and research hospitals (Cucino et al, 2021;Hockaday and Piccaluga, 2021;Micozzi et al, 2021;Muscio et al, 2016;Sciarelli et al, 2022). In particular, Netval every year performs a survey of Italian universities, public research organizations, and research hospitals to monitor their technology transfer activities.…”
Section: Research Methodology 31 Sample and Data Collectionmentioning
confidence: 99%
“…This was due to the fact that within entrepreneurial universities, there is space for an effective dialogue between various educational, scientific, business and public authorities (Gogorishvili and Zarandia, 2021;Seturidze and Topuria, 2021; Vesperi and Gagnidze, 2021b). Moreover, these authorities can quickly commercialise research, introduce the results to the market, and retrain fully qualified specialists (Guerrero et al, 2016;Kharadze et al, 2021;Lekashvili and Bitsadze, 2021;Papachashvili et al, 2021;Sciarelli et al, 2022;Sobolieva et al, 2021). Due to their relevance, below a few key factors have been identified that contribute to the efficient functioning of entrepreneurial universities, namely: the creation of an "entrepreneurial environment, entrepreneurial staff as well as entrepreneurial teaching and learning; a strong entrepreneurial vision and the presence of leaders; the need for an environment of awareness to support spin-off creation; identifying factors that determine continuous organisational success" (Dominici and Gagnidze, 2021, p. 24).…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%
“…, 2016; Kharadze et al. , 2021; Lekashvili and Bitsadze, 2021; Papachashvili et al., 2021; Sciarelli et al. , 2022; Sobolieva et al.…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%